Impacto da manutenção de reprodutores de macrobrachium rosenbergii na qualidade da água - Peixoto Henares, Matheus Nicolino [UNESP]; Monteiro Camargo, Antonio Fernando [UNESP]; Vicente Biudes, Jose Francisco [UNESP]; Valenti, Wagner Cotroni [UNESP] (Inst Pesca, 2011)
Our objective was to evaluate the impacts caused on pond water quality by maintenance of Macrobrachium rosenbergii broodstock. During eight weeks we determined pH, dissolved oxygen (DO), conductivity, turbidity, particulate suspended material (PSM), nitrogen (N) and phosphorus (P), all in inlet and effluent water. All variables presented higher values in the effluent, except OD. N-ammoniacal concentration (0.013 mg L(-1)) was 2.7 times higher in the effluent pond; NO(2)-N (0.019 mg L(-1)), 2.3; NO(3)-N (0.139 mu g L(-1)), 1.8; PO(4)-P (0.065 mg L(-1)), 7.2; and DP (0,104 mg L(-1)), 4.9 times higher. For TKN (0.67 mg L(-1)) and TP (0.235 mg L(-1)) the values in the pond effluent represent an increase of 0.27 mg L(-1) and 0.175 mg L(-1), respectively. The maintenance of M. rosenbergii broodstock increase the nutrient concentrations, mainly TP, prevent effluent pond released into receiving water bodies on 1, 2 and 3 classes of the CONAMA N degrees 357 Resolution.
Impact of maintenance of Macrobrachium rosenbergii broodstock prawn on water quality
Keywords: Effluent; water quality; prawn farm activity; crustacean; nutrients